(untitled) - Schneider, G. Michael (Boston, MA, 2010)
This revision of Schneider and Gersting's bestselling text now offers a more flexible approach to the CS0 course. The text still features a solid introduction to programming concepts, but the language-specific material has been moved online and expanded. In addition to modules for C++ and Java, optional modules for C#, Python, and Ada are now available. The text also includes new chapters on Security and Entertainment, expanded coverage of wireless networks, and updated feature boxes.
Keywords: Computer science,Java (Computer program language); Java (Ngôn ngữ lập trình máy tính)